Determinan Transfer Pricing Dengan Debt Covenant Sebagai Pemoderasi - Lukmanul Hakim; Tri Widyastuti; Dwi Prastowo Darminto; Darmansyah Darmansyah (ITB AAS INDONESIA, 2022)
This study aims to conduct research on the determination of transfer pricing with the debt covenant as a moderator. The factors that determine transfer pricing in this study are the effective tax rate, tunneling incentive, exchange rate and good corporate governance. The sample used in this study consisted of 33 manufacturing companies in 2017-2020 with purposive sampling method. The method used in this research is quantitative method with Moderated Regression Analysis data analysis technique. The results showed that the effective tax rate had no effect on transfer pricing, while tunneling incentives, exchange rates and good corporate governance had an effect on transfer pricing. Debt covenants can moderate the effect of tunneling incentives on transfer pricing, but debt covenants cannot moderate the effect of effective tax rates, exchange rates and good corporate governance on transfer pricing